KESALAHAN PEMBENTUKAN FRASE NOMINAL BAHASA ARAB OLEH PEMBELAJAR BAHASA ARAB (Studi Kasus pada Mahasiswa Fakultas Adab) - Ubaidillah Ubaidillah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2009)
The research is aimed to describe the types of grammatical errors, especially the process of forming Arabic noun phrases (NP) done by students of Department of Arabic Language and Literature of State University for Islamic Studies Sunan Kalijaga Yogyakarta, and to explain the factors that influence those errors. The data of this study is taken from the result of writing exam in the class of kitābah muhakkamah or 'academic formal writing' of the fifth semester. The method, which is used to describe the grammatical errors, especially the making process of Arabic NPs, is the method of error analysis. The result of the analysis shows that the frequency of errors in the process of forming the Arabic NPs, which happens repeatedly, is when the patterns of NP are noun+noun (N+N) and noun+adjective (N+Adj). The error of NP with a pattern of N+N happens when the article (al-) at head noun is used, while the error of NP with a pattern of N+Adj happens when the article (al-) at head noun, which has definite modifier, is omitted. The factors, which influence the making errors of Arabic NP, are grammatical factors. The grammatical factors are caused by the different rules between the Indonesian and Arabic NP. On the other hand, the process of language acquisition of second or foreign language makes these problems worse.